Efektivitas Acceptance and Commitment Therapy Terhadap Resiliensi Korban Bencana Alam yang Mengalami Kecacatan Fisik - Wirmando Wirmando; Alfrida Alfrida; Jenita Laurensia Saranga'; Anita Sampe; Asrijal Bakri; Yulta Kadang (LPPM Hang Tuah Pekanbaru, 2022)
Being physically disabled due to a natural disaster is a traumatic experience in a person's life that can make a person feel slumped and helpless in his life. It takes a psychotherapeutic intervention such as Acceptance and Commitment Therapy (ACT) to foster resilience of victims of natural disasters who have physical disabilities in order to be able to bounce back, be productive, and be able to play their role again in society. The purpose of this study was to analyze the effect of ACT therapy on increasing the resilience of victims of natural disasters in Sigi who experienced physical disabilities. The research method used is quasy experiment with a one group pre-post test approach. The number of samples in this study was 22 respondents collected using purposive sampling techniques. This research was conducted in August-September 2022 in Sigi Regency, Central Sulawesi Province. The statistical test used is the Wilcoxon test. The results of this study showed that there was an effect of ACT therapy on increasing respondents' resilience (p=0000). In addition, this study showed that after being given ACT therapy, most respondents' resilience was in the high category (59%). This study indicates that a person who experiences a traumatic event such as a physical disability due to a natural disaster will face a difficult time in life, psychological vulnerability and the ability to cultivate low resilience. Therefore, it is important for health providers to pay attention to psychological aspects, as well as provide psychotherapeutic interventions such as ACT to victims of natural disasters, especially those who experience physical disabilities in the rehabilitative phase so that they can accept themselves, be committed, productive, and return to play their role in society